THE ROLE OF SOCIAL NETWORKS IN TEACHING - Sobirova Shahzoda Dilshod qizi; Shahlo Kamalova (Bright Mind Publishing, 2025)
Social networks have become important tools in modern education, reshaping traditional methods of communication and learning. This article examines how platforms such as Facebook, Instagram, Twitter, and LinkedIn contribute to interactive learning environments, support educational communities, and encourage student engagement. It also discusses the advantages and potential challenges of integrating social media into teaching practices.
Keywords: Social media, digital learning, student engagement, online collaboration, educational networks.